Pengaruh Arus Kas Operasi dan Laba Bersih pada Dividen Kas : Studi pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2015 – 2019 - Rudi Andrean; Destia Pentiana; Dian Nirmala Dewi (Politeknik Negeri Lampung, 2022)
This study aimed to determine the effects of operating cash flows and net income on dividend cash. The hypothesis taken was that H1 was the effect of operating cash flow on cash dividends and H2 was the effect of net income on cash dividends. The population of this study were food and beverage companies registered in Indonesia Stock Exchange (IDX) in 2015 – 2019. The sampling method used in this study was purposive sampling, that is sample selection with certain criteria. Eight companies that met the criteria were obtained, so the total sample size was 40 samples. The data collection technique used in this study was secondary data documentation obtained by downloading financial reports published by www.idx.co.id. The data analysis technique used was multiple linear regression test by using SPSS 22. The results of this study indicate that operating cash flow has no significant effect on cash dividends, while net income has a significant effect on cash dividends.